Quality of Olympics opening ceremony: Tourism behavioural intention of international spectators. Issue 2 (4th March 2019) - Choi, Il-young; Choi, Hyun-ju; Lee, Jong-yoon; Jung, Seung-hye; An, Byong-ju; Kim, Joon-ho
Abstract : This study assessed the impact of the artistic program of the Winter Olympics opening ceremony event on international spectators' national image branding of the host country and their intention to visit the host nation. We surveyed a total of 600 international spectators of the South Korea PyeongChang Winter Olympics Opening Ceremony (150 Filipino, 150 Americans, 150 British, and 150 South Africans; 50% female) on their perceptions of quality of the opening ceremony, national image branding, and their intention to visit the host country. Results from hierarchical analysis indicated that the quality of the artistic program of the PyeongChang Winter Olympics opening ceremony (content of expression, form of expression, and narrative of nation) predicted perceptions of host country national image and behavioural intentions to visit. From these findings, we conclude that the artistic program of the opening ceremony of an Olympic event is a valuable opportunity to help international spectators to better understand the host country culture, and for influencing their tourism intentions.